Considering Inclusive Education through the Independent Living Movement: Lessons for Improvement?. Issue 4 (26th August 2020) - Danforth, Scot; Connor, David J.
Abstract: In this article, we focus on the life and accomplishments of Ed Roberts, leader of the Independent Living Movement for people with severe disabilities, to consider ways he envisioned and enacted a radical shift in professional practices within the field of rehabilitation. Using the field of rehabilitation as an adult parallel to the field of Special Education, we invite readers to contemplate ways in which the independent living movement can hold potential lessons for how inclusive education is conceptualized and implemented, as well as offering some suggestions of our own.